The Influence of The Amount of Third Party Funds and Inflation on The Placement of SME Financing in the BMT Sharia Cooperative of The Civil Society of North Sumatra. - Pradesyah, Riyan; Reza Ayu Ardianti (International Journal of Educational Research & Social Sciences, 2021)
This study discusses the allocation of financing distributed by the Madhani Community BMT to Small and Medium Enterprises (SMEs), taking into account several variables used, namely Third Party Funds, Inflation and Financing Allocations. This study aims to see the simultaneous effect of third party funds and inflation on the allocation of financing for small and medium enterprises. The research method used in this study is quantitative, with data analysis using SPSS. As for the results of the study, that third party funds (TPF) partially have no effect and are not significant on SME financing, because the value of t count < t table (0.132 < 2.012) and the significance level is greater than 0.05. While the inflation variable has an effect and is significant, on SME financing seen from the value of t count < t table (5.801 > 2.012) and the significant level is less than 0.005. Meanwhile, simultaneously, Third Party Funds and Inflation have an effect on the Financing of SMEs in the BMT for the Civil Society of North Sumatra.